9-Fluorenylmethyl (Fm) Disulfides: Biomimetic Precursors for Persulfides - Park, Chung-Min (Org Lett, 2016)
[Image: see text] The development of a functional disulfide, FmSSPy-A (Fm = 9-fluorenylmethyl; Py = pyridinyl), is reported. It can effectively convert small molecule and protein thiols (−SH) to form −S-SFm adducts under mild conditions. This method allows for a H(2)S-free and biomimetic protocol to generate highly reactive persulfides (in their anionic forms). The high nucleophilicity of persulfides toward a number of thiol-blocking reagents is also demonstrated. The method holds promise for further understanding the chemical biology of persulfides and S-sulfhydration.